Secondary hemophagocytic lymphohistiocytosis: a case report - Salvati, Lia; Di Renzo, Anita; Moscardelli, Sergio; Natali, Laura; Claudio, Ferri; Viscido, Angelo (Acta Biomedica Atenei Parmensis, 2021)
Hemophagocytic lymphohistiocytosis (HLH) is a rare hematologic syndrome presenting either as an inherited life-threatening inflammatory disorder in children or as a secondary disease in adults. Inherited HLH involves inborn defects in lymphocytes and includes autosomal recessive and X-linked disorders characterized by uncontrolled activation of T cells and macrophages and overproduction of inflammatory cytokines. Secondary or acquired HLH occurs in the settings of infections, systemic connective tissue disease and lymphoid malignancies, possibly due to underlying genetic predisposition to develop HLH. The mechanisms leading to secondary HLH have yet to be fully determined and the disease remains frequently undiagnosed and thereby untreated. Herewith we report the case of an 83-year old Caucasian male who referred to our Division of Internal Medicine and Nephrology due to marked asthenia associated with fever, mental confusion, drowsiness and hyporexia, who was ultimately diagnosed with HLH secondary to anaplastic B cell lymphoma. This case report illustrates the difficulties in the diagnostic workup of HLH, mainly related to early identification of the underlying disease and rapid instauration of appropriate therapy.